Specialization on a technologically atagnant aector need not be bad for growth - Gabriel Felbermayr (Johannes Kepler University of Linz, Department of Economics, 2004)
This paper presents a simple North-South model of endogenous growth, based on learning by doing, which is consistent with the following empirical observations: (i) the price of investment goods relative to consumption goods has been falling for the last 40 years in most industrialized countries, (ii) poor countries are net importers of investment equipment and (iii) after a period of initial convergence, the sample of open economies exhibits remarkable stability of the per capita income distribution. In contrast to the research tradition started by Lucas (1988), in the proposed model, specialization on the technologically stagnant consumption sector does not entail a growth penalty.
Keywords: F43; O41; 330; endogenous growth; AK model; international trade; embodied technical change; Nord-Süd-Beziehungen; Internationale Arbeitsteilung; Neue Wachstumstheorie; Schrumpfungsbranche; Mehr-Sektoren-Modell; Lernprozess; Entwicklungskonvergenz; Theorie